PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN MENGGUNAKAN PENDEKATAN DISCOVERY DI KELAS IV SD NEGERI 07 TALAWI MUDIK KECAMATAN TALAWI KOTA SAWAHLUNTO - RUMJASMI RUMJASMI (JURNAL MANAJEMEN PENDIDIKAN, 2019)
This research is based on the results of observations and interviews conducted by researchers with grade IV teachers at SD Negeri 07 Talawi Hilir, Talawi Subdistrict, Sawahlunto City on January 25, 2015 encountered problems, so far the teacher has not used the discovery approach in learning, teachers dominate learning more without involving student activity in learning. This study uses qualitative and quantitative approaches, with type (CAR), the study was conducted in two cycles, with the stages of planning, implementation, observation and reflection. The steps of discovery learning are: 1) orientation, 2) formulating problems, 3) formulating hypotheses, 4) testing hypotheses, 5) analyzing and presenting data in the form of reports or conclusions and, 6) applying conclusions in everyday life. This study shows an increase in student learning outcomes in social studies learning, by using the Discovery approach, this can be seen, both from the ability of teachers to design learning from 81% to 97% increase level, teacher activity from 71% has increased 96%, activity students from 50% experienced an increase to 92%. And from the completeness of student learning outcomes before using the Discovery approach is 40%, after the first cycle of the first meeting there was an increase of 50%, and in the first cycle of the second meeting there was still an increase of 65% and in the second cycle the first meeting was 75% and finally in the second cycle the second meeting showed better results, namely 85%.